Knowledge mining for the differentiation pattern with respect to the productivity and trophic status of some selected lakes of Western Himalayas - Kumar, Rakesh; Jindal, Rajinder; Kulharia, Mahesh; Sharma, Amit Kumar; Thakur, Kushal; Brar, Bhavna; Mahajan, Danish; Sharma, Ankita; Kumar, Sunil; Sharma, Dixit (Frontiers in Environmental Science, 2023)
The present study deals with an account of the primary productivity and trophic status of Rewalsar, Kuntbhyog, and Prashar lakes of Western Himalayas. Seasonal variations in gross primary productivity (GPP) (g C m–2 day–1), net primary productivity (NPP, respiration (R), and the NPP/R ratio have been studied and compared with hydrobiological factors. Among various factors, temperature, light, nutrients, and chlorophyll a were accountable for high productivity. Nygaard’s trophic state indices were calculated. GPP showed a positive relationship with water temperature, penetration of light, nitrate, and with phosphate. The extensive range of the compound index observed in Rewalsar (12.00–20.00) and Kuntbhyog lakes (12.50–18.00) confirmed their eutrophic nature. Based on the trophic classification of waters and on the basis of productivity, Nygaard’s trophic state indices, and richness of nutrients, Rewalsar and Kuntbhyog lakes could be categorized as eutrophic, whereas Prashar Lake, as oligo-eutrophic. Based on the presence, absence, frequency of appearance, and abundance of different organisms recorded during the present investigation, bioindicators of trophic status have been determined.